ANALYSIS OF QUALITY CONTROL METHODS IN THE FURNITURE FACTORY "DIVA DIVANI" VRANJSKA BANJA - Stanojevic, Damjan; Temelkova, Anastasija; Jevtoska, Elena; Trposki, Zoran (FDTME-Skopje, 2025)
The goal of the research presented in the paper is the analysis of various quality control procedures in a factory that produces upholstery products. The upholstery industry is very developed in Vranje, the competition is high, so quality control has a huge impact on the company's operations. Quality control is one of the key elements in the production management system in a furniture factory. Its role is to ensure that each product meets defined technical, aesthetic and functional requirements, as well as the expectations of end users. Establishing systematic quality control — from incoming control of raw materials, through process control at all stages of production, to final control of finished products — enables the detection and elimination of defects at an early stage, thereby significantly reducing the costs of repairs and complaints. This paper presents a complete quality control system in a furniture factory, from start to finish, and presents the conclusions reached, as well as their implementation for the better business of the company
Keywords: quality system, furniture, wood technology